Trust and Subjective Norms to Optimize Loyalty to Influencers through Social Exchange Theory - Fauziah, Salisa; Marsasi, Endy Gunanto (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
This study uses social exchange theory to determine the role of expertise, authenticity, and subjective norms on trust in optimizing product attitude, loyalty to influencers and purchase intention. Social exchange theory considers the impact of the relationship between two individuals. Researchers added subjective norms as a novelty in this study. The object of the research focuses on perfume products. The subjects in this study were Generation Y and Z. Researchers used a quantitative approach, primary data was collected by distributing questionnaires using purposive sampling. The analysis technique used the Structural Equation Modeling (SEM) test. The results showed that the relationship between subjective norms on trust and trust on product attitude, loyalty to influencers, and purchase intention has a positive and significant influence. The relationship between expertise and authenticity variables to trust has an insignificant effect. These findings provide important insights for companies to develop social media marketing strategies that utilize subjective norms and trust to build product attitudes, loyalty to influencers, and purchase intention.